The Impact of Supply Chain Risk Management Practices on Performance During COVID-19 Pandemic - ABDEL-RAHMAN, LAMA AMIR FAIK (İstanbul Kültür Üniversitesi, 2023)
This study investigates the role of supply chain risk management (SCRM) in mitigating the effects of disruptions on the supply chain's (SC) resilience and robustness in the context of the COVID-19 outbreak. Even though few studies have been conducted in this field, it appears to have varying effects depending on the country and sector. With this motivation, data from 102 Turkish pharmaceutical firms are collected and analyzed using confirmatory composite analysis (CCA) based on partial least square structural equation modelling (PLS-SEM). The results of the hypothesis analysis show the negative impact of COVID-19 disruption on SCRM practices, SC resilience, and SC robustness, which demonstrates the negative impact of the epidemic on the practices of SCRM, and their abilities to regain their SC's performance after absorbing the disruption effects. COVID-19 appears to have a negative impact on how firms identify and control SC risks due to the amplitude of sudden global disturbances that few firms were able to predict in advance. The findings indicate that COVID-19 disruption impacts have mainly affected SC resilience. However, SC robustness was not directly affected by disruption impacts, as most of the firms seemed to think that they would be able to maintain their planned performance after the disruption. Furthermore, the findings reveal the mediating role of SCRM practices and the prominent role they play in fostering supply chain resilience and robustness.
COVID-19 Pandemisi Döneminde Tedarik Zinciri Risk Yönetimi Uygulamalarının Performansa Etkisi
▪ Yüksek lisans tezi.
Keywords: Supply Chain Risk Management Practices; Supply Chain Robustness; Supply Chain Resilience; COVID-19; Epidemic; CCA; PLS-SEM